Vlakno cave on Dugi otok (In situ, 2024)
The paper presents the results of archaeological research conducted in Vlakno cave on Dugi otok during 2023 within the EpiC project of the Croatian Science Foundation (IP-2019-04-6115).
Keywords: Vlakno cave; Dugi otok; Palaeolithic; Epigravettian; lithics